The impact of job stress on perceived professional benefits among Chinese nurses caring for patients with gynecological cancer: mediating effects of perceived social support and self-efficacy - Zhang, Yuxin; Meng, Xinhai; Zhou, Lihua (Frontiers in Psychology, 2024)
Introduction Nurses caring for patients with gynecological cancer experience significant job stress, which adversely impacts their mental health. Previous studies have indicated that perceived professional benefits serves as a protective factor for nurses’ mental health, and factors such as job stress, perceived social support and self-efficacy influence their perceived professional benefits. However, the relationships between these factors and the associated mechanisms have remained incompletely understood. This study explored the role of perceived social support and self-efficacy in job stress and perceived professional benefits among nurses caring for patients with gynecological cancer. Methods During June and July 2023, an investigation was conducted in Anhui Province. The Nurse Job Stressors Scale, Perceived Social Support Scale, Nurses’ Perceived Professional Benefits Questionnaire and General Self-Efficacy Scale were administered to 311 nurses caring for patients with gynecological cancer. A chained-mediated effect model was constructed and validated. Results Job stress negatively affected nurses’ perceived professional benefits. Perceived social support was a mediator in job stress and nurses’ perceived professional benefits, with a mediating effect value of −0.093. Additionally, perceived social support and self-efficacy functioned as sequential mediators in this relationship, with a mediating effect value of −0.032. Conclusion This study unveils the influencing mechanisms of job stress on perceived professional benefits of nurses caring for patients with gynecological cancer. It is essential for nursing managers to alleviate nurses’ job stress, provide sufficient and effective social support and improve their self-efficacy, ultimately enhancing their perceived professional benefits.